Estudo fitoquímico e alelopático de extratos de Diaporthe phaseolorum - Accarini, Raissa Barcha (2021)
Endophytic fungi have the ability to live inside or outside a plant tissue, without harming it. Studies have shown that these groups of fungi are promising sources in the search for new natural compounds, since in many of them, antifungal, antibacterial, antioxidant and phytotoxic activities were found, being of great interest for applications in medicine, agriculture and chemical biology. In this work, the fungus Diaporthe phaseolorum, extracted from healthy leaves of Serjania lethalis A.St-Hils, a liana belonging to the Sapindaceae family commonly found in the Brazilian cerrado, was used. already published. Fungi of the genus Diaporthe, whose asexual state is known as Phomopsis, are found as endophytic and saprophytic in a variety of plant species, and produce compounds with known phytotoxic and cytotoxic activities, such as gulypyrones and phomoxanthones, but there are still few studies with the species Diaporthe phaseolorum. Therefore, the main objectives of this work were to evaluate the phytotoxic potential of extracts and fractions of D. phaseolorum on indicator and invasive target species, analyzing their mode of action, as well as identifying secondary metabolism compounds. First, two extracts were prepared, one mycelial (EME) and the other from the culture medium (EMC), extracted with ethanol and ethyl acetate by liquid-liquid partition, respectively. Both extracts were tested in bioassays that evaluated the growth of wheat coleoptile (Triticum aestivum L.), germination and seedling growth of mono and eudicotyledonous invasive and indicator species: wild poinsettia (Euphorbia heterophylla L.), colony grass (Megathyrsus maximus J.), onion (Allium cepa L.) and sesame (Sesamum indicum L.), respectively, and were also tested in a bioassay that evaluates the growth of sesame (Sesamum indicum L.) root metaxylem cells. The extracts were fractionated on a silica column in normal phase and their respective fractions were again tested on the growth of wheat coleoptiles in order to select those with greater phytotoxicity. Taking into account the results and yields, fraction 9 (EME9) from the mycelial extract (EME) was selected for the seedling growth and germination bioassays and for the sesame root metaxylem cell growth bioassay. Both crude extracts (EME and EMC) used in the wheat coleoptile growth bioassay were able to inhibit their growth, showing their highest percentages of inhibition when used at their highest concentrations (0.8mg/mL-1 ), as the fractions EME9 and EME3 from the crude mycelial extract were those with the highest inhibitory percentages for the same bioassay. In the seedling growth bioassay, the crude extract (EME) and its fraction (EME9) were able to inhibit the growth of both aerial parts and roots of wild poinsettia seedlings. Wild poinsettia was also more sensitive to mycelial extract and its fraction in relation to germination percentage, showing the lowest percentage values. The growth of sesame seedling root metaxylem cells was also inhibited, proving the phytotoxic effect of the mycelial extract and its respective fraction to them. Through a chemical analysis by CLUE (ultra-efficiency liquid chromatography) performed on samples EMC, EME and EME9, 7 major compounds were identified, all already described in the literature for the genus Diaporthe, where the compound fomoxantone A is the one to be present in larger quantity and in all analyzed samples. The crude extracts EMC and EME and the EME9 fraction showed phytotoxic activity in the bioassays performed in this study, inhibiting the growth of wheat coleoptiles, roots and aerial parts of the target species and sesame root metaxylem cells. Thus, compounds identified in the extracts of Diaporthe phaseolorum show promise in the study of their bioactivities, since studies with the species related to this bioactivities are scarce in the literature.